The impact of customer due diligence in the Islamic banking institutions in Malaysia: a legal perspective - Raja Alias, Raja Madihah; Mohd Yasin, Norhashimah; Ng, See Teong (Centre for Contemporary Fiqh and Shariah Compliance, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 43600 UKM Bangi, Selangor, Malaysia, 2018)
The money laundering and terrorism financing are the financial crimes that caused global threat to the financial integrity and economic activities of the country. In combating these financial crimes, the international standards imposed by the Financial Act ion Task Force (“FATF”) requires that all financial institutions in all countries to undertake the Customer Due Diligence (“CDD”) as its preventive measurements in combating these financial crimes. In Malaysia, this CDD requirement is regulated under Section 16 of the Anti-Money Laundering, Anti-Terrorism Financing and Proceeds of Unlawful Activities Act 2001 (Act 613) (“AMLATFPUAA”). This CDD requirements is applicable to all the ‘Reporting Institutions’ listed under the First Schedule of the AMLATFPUAA which includes the Islamic banking institutions in Malaysia. As such, the legal requirements provide that there is no exception for the Islamic banking institutions to follow this statutory requirement. Therefore, the objective of this paper is to highlight the standards in conducting CDD requirements on the Islamic banking institutions in Malaysia. This paper is significant by emphasising the Policy Document on conducting CDD under the ‘Anti- Money Laundering and Counter Financing of Terrorism (AML/CFT)- Banking and Deposit- Taking Institutions (Sector 1)’ which is set out by the Central Bank of Malaysia (“BNM”). This paper employs library based research by analysing the primary and secondary legal sources on CDD standards and legal requirements. This paper suggests that the Islamic banking institutions in Malaysia are in compliance with the international standards on CDD as imposed by the FATF and the statutory obligations under the AMLATFPUAA. Therefore, continuous efforts by the Islamic banks in Malaysia are required in combating these financial crimes.